The borderland of neuromyelitis optica. - Matthews, L; Baig, F; Palace, J; Turner, M (2009)
Neuromyelitis optica (NMO), also known as Devic's disease, is an emerging clinical and pathological entity originally thought to be a variant of multiple sclerosis. Characterised by episodes of demyelination confined to the optic nerve and spinal cord, the discovery in such patients of antibodies to the aquaporin-4 channel has been largely responsible for defining the phenotype to date. Recently it has become clear that there is a borderland where there are patients with optic neuritis-only and myelitis-only forms of the disease, and these may be seronegative in the early phase. We describe two cases of optic neuritis-only NMO, and explore the current understanding of the diagnosis and spectrum of NMO disorders.